Social Anxiety, Fear of Negative Evaluation, and Distress in a Virtual Reality Environment - Sigurvinsdottir, Rannveig; Soring, Karen; Kristinsdottir, Karen; Halfdanarson, Sveinn Gunnar; Johannsdottir, Kamilla R.; Vilhjalmsson, Hannes H.; Valdimarsdottir, Heiddis B. (Behaviour change, 2021)
According to cognitive theories of social anxiety, fear of negative evaluation (FNE) may be the mechanism whereby social anxiety induces distress. However, studying this can be challenging, as individuals with social anxiety may be reluctant to enter anxiety-provoking social situations, such as speaking in front of others. The present study used virtual reality (VR) to examine if giving a presentation in front of a virtual audience induced distress among undergraduate students and to test the hypothesis that FNE would mediate the relationship between social anxiety and distress. University students ( N = 58, 70% female) entered a VR environment where they stood in front of a virtual audience and gave a short, impromptu presentation about their university. Participants also completed self-report measures of social anxiety, FNE, and distress (estimated before, during, and after VR). Distress and FNE had positive relationships with social anxiety and FNE fully mediated the relationship between social anxiety and distress. As far as we are aware, this is the first VR study to show this effect. The findings indicate that FNE could be a useful treatment target to reduce distress when presenting in front of an audience, either in VR or in person.